Teaching methodology, stress and study and learning strategies: interrelationships among university students - Guedes-Granzotti, Raphaela Barroso; César, Carla Patrícia Hernandez Alves Ribeiro; Ribeiro, Vanessa Veis; Dornelas, Rodrigo; Moreira, Patricia Pinatti; Silva, Kelly da (Paidéia (Ribeirão Preto), 2021)
Higher education can be offered by traditional or active teaching methodology, which can influence differently the study and learning strategies and the stress level of university students. This study aimed to investigate the study and learning strategies and the prevalence of stress among students of active and traditional teaching methodology and verify the influence of stress on using these strategies. 210 students in speech, language and hearing sciences from a Brazilian Federal University participated, divided into two groups, TMG (traditional methodology) and AMG (active methodology). They responded to Learning And Study Strategies Inventory and Lipp’s Stress Symptom Inventory for Adults. The teaching methodology influenced the study and learning strategies, but not the stress. Stress interfered differently in the study and learning strategies depending on the teaching methodology.